Obstetrical and perinatal consequences of childbirth in women with antenatally undiagnosed fetal growth restriction - V. A. Puchkov; M. I. Pavliuchenko; O. A. Bohomolova (Сучасні медичні технології)
Fetal growth restriction (FGR) is one of the most studied topics in the medicine of the mother and fetus. However, not identified antenatally FGR can have an increased risk of both perinatal morbidity and mortality, as well as adverse long-term consequences. The identification of FGR during pregnancy will contribute to the reduction of both perinatal morbidity and perinatal mortality.